Ride like the wind - Berenstain, Stan 1923-2005.; Berenstain, Jan, 1923- (New York : Random House, 2002)
Sister Bear falls in love with horses and takes riding lessons on a horse named Old Bess.
"A Stepping Stone book."
190
Accelerated Reader AR
Keywords: Horses -- Fiction; Horsemanship -- Fiction; Bears -- Fiction